NILAI PERUSAHAAN: Manifestasi Dari Fundamental Keuangan Perusahaan - Martono Martono; Muhammad Yusuf; Setianingsih Setianingsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Companies as profit institutions always have a way to increase the wealth of shareholders, one of which is by increasing the value of the company in the eyes of the public. However, to achieve this the company is required to demonstrate its performance through financial reports. This study aims to analyze firm value in the food and beverage business group by looking at the company's financial fundamentals, such as assets, capital and profitability. The research method uses quantitative with the concept of multiple linear regression statistical analysis. The data were collected purposively, namely the sampling technique which applies the requirements for the collection. The results showed that the company's financial fundamentals had a real contribution to the increase in firm value. Interestingly, the simultaneous model shows a positive direction. This means that the value of companies in the food and beverage business group is strongly influenced by the company's financial condition, particularly assets, capital and profits.